Effect of mass rearing on the genetic diversity of the predatory mite Amblyseius swirskii. Issue 7 (17th July 2019) - Paspati, Angeliki; Ferguson, Kim B.; Verhulst, Eveline C.; Urbaneja, Alberto; González‐Cabrera, Joel; Pannebakker, Bart A.
Abstract: Amblyseius swirskii Athias‐Henriot (Acari: Phytoseiidae) is a predatory mite used to control whiteflies and thrips in protected crops. This biocontrol agent, originating from the Eastern Mediterranean region, has been mass‐reared for commercial use since 2005 and is widely used in augmentative biocontrol programs. As a polyphagous predator, it has to cope with different biotic and abiotic factors. However, possible adaptation to mass rearing for production might be hindering its resilience and capacity for optimum performance in the field. In this study, we investigated the effect of long‐term mass rearing on the genetic diversity of A. swirskii . We identified six microsatellite loci from whole‐genome nanopore sequencing of A. swirskii and used these in a comparative analysis of the genetic diversity and differentiation in eight wild populations collected from Israel in 2017 and a commercially available population. Our results indicate that the commercial population is 2.5× less heterozygous than the wild A. swirskii . Furthermore, the commercial population has the highest genetic differentiation from all the natural populations, as indicated by higher pairwise Fst values. Overall, we show that commercially reared A. swirskii have reduced genetic variation compared to their wild counterparts, which may reduce their performance when released to control pests in an integrated pest management (IPM) context. Abstract : Long‐term adaptation to mass rearing can reduce the genetic variation in commercial biocontrol agents. In this study, we identified six microsatellite loci from whole‐genome nanopore sequencing of Amblyseius swirskii (Acari: Phytoseiidae) and estimated the genetic diversity of wild and commercial populations. We show that commercially reared A. swirskii have reduced genetic variation compared to their wild counterparts, which may reduce their performance when released to control pests.